Radar sea clutter : modelling and target detection - Rosenberg, Luke; Watts, Simon, 1949- (Radar, Sonar and Navigation Ser., 2022)
This book presents comprehensive coverage of new research into sea clutter characterisation and modelling, radar performance prediction and maritime target detection. The book also includes a summary of sea-clutter scattering characteristics and datasets provided that can be used for modelling.